Feasibility of Food and Beverage Taxation to Tackle Overweight and Obesity in Thailand: Stakeholders’ Views from the Public Hearing - Phonsuk, Payao; Phulkerd, Sirinya; Thamarangsi, Thaksaphon (Journal of Health Science of Thailand, 2017)
Taxation on food and beverage has been regarded as a “Good Buy” intervention, by WHO, to tackle the increasing epidemic of overweight and obesity. The public hearing on ‘the feasibility of introducing unhealthy food and beverage taxation to tackle overweight and obesity in Thailand’ provided various opinions and comments from different points of view on the possibility to develop food and beverage taxation. A comprehensive and fair tax policy covering wide range of food and beverage items, together with price subsidization policy on agricultural products are preferable approach. Sweetened beverage has the highest feasibility to be the starting point. Groundwork to promote the preparedness is required to enhance success. These include generation and utilization of technical evidence, setting clear and appropriate objective, and introducing taxation policy along with other public approaches. Major challenges of introducing food and beverage taxation in Thailand were raised by relevant stakeholders, for example, how to shift the main purpose of taxation to address health problem, measuring policy impact on dietary behaviours, monitoring system and economic evaluation, and addressing different interests from different stakeholders. Therefore, strong support as well as inter-sectoral collaboration between public, private sector and civil society, is a key to increase feasibility of food and beverage taxation policy on mitigation of overweight and obesity problem.